I have to solve the equation:
[tex] |4 \sqrt{2} - 6 | + |2 \sqrt{10} - 6| [/tex]
The first thing I tried is simply removing the modules, it seemed like the most logical solution and this is the answer I got, but it wasn't any of the options:
[tex]4 \sqrt{2} + 2 \sqrt{10} + 12[/tex]
The second thing I tried is putting both equations in one module and sum the first one with the second one in parentheses like this:
[tex] |4 \sqrt{2} - 6 + (2 \sqrt{10} - 6 | = \\ = |4 \sqrt{2} - 6 + 2 \sqrt{10} + 6 | = \\ = 4 \sqrt{2} + 2 \sqrt{10}[/tex]
But this wasn't in the answers either.
After I checked, the correct answer was:
[tex]2 \sqrt{10} - 4 \sqrt{2} [/tex]
So I was wondering where does the minus come from?

It is in a module and between the modules, there's a plus and even if that plus somehow turns into a minus when it goes inside the modules, which I'm not aware of, it would still turn into a plus because it is in a module ;-; Or I'm just st*pid, I don't know. ​

Respuesta :

Think back to the definition of absolute value:

• If x ≥ 0, then |x| = x.

• If x < 0, then |x| = -x.

In other words, the absolute value always returns a positive number. So if x is positive, leave it alone; but if it's negative, then you have to negate it to get a positive number back.

This means that you cannot simply reduce |x - y | to x - y because you need to consider the possibility that x - y may be negative, in which case |x - y | would reduce to -(x - y) = y - x.

In this case,

|4√2 - 6| = -(4√2 - 6) = 6 - 4√2

because 4√2 < 6, which you can determine by comparing both of these numbers as square roots:

4√2 = √16 √2 = √32

6 = √36

and √32 < √36 because 32 < 36.

Similarly,

|2√10 - 6| = 2√10 - 6

because

2√10 = √4 √10 = √40

6 = √36

So ultimately,

|4√2 - 6| + |2√10 - 6| = (6 - 4√2) + (2√10 - 6) = 2√10 - 4√2

ACCESS MORE